1H and 13C NMR assignments of dihydropipataline, the main of four long-chain 1-(3, 4-methylenedioxyphenyl)-alkanes from Piper darienence D.C. Issue 4 (2000) - Meléndez-Rodríguez Meléndez-Rodríguez, Myriam Myriam; Rendón Rendón, Willy Willy; Chávez Chávez, Galia Galia; Martínez-Guajardo Martínez-Guajardo, Gerardo Gerardo; Joseph‒Nathan Joseph‒Nathan, Pedro Pedro
Abstract : Four 1-(3, 4-methylenedioxyphenyl)-alkanes having linear ten, eleven, twelve and fourteen carbon atom chains, found in the roots of Piper darienence D.C., were separated by HPLC and their structures determined by mass spectrometry and NMR spectroscopy. Conventional 1D NMR methods were used for 1 H chemical shifts assignment of the main compound dihydropipataline (3 ) [1-(3, 4-methylenedioxyphenyl)‒dodecane]. The 13 C NMR assignment was carried out using conventional considerations and 2D NMR techniques (HETCOR and FLOCK) in combination with spectral 13 C NMR simulation and ab initio DFT-GIAO NMR calculations.